Trans-Frontal Five-Fluorouracil (TraFFF): a novel technique for the application of adjuvant topical chemotherapeutic agents in sinonasal adenocarcinoma. (24th October 2018) - Singh, Narinder; Wong, Eugene; Huang, Johnson; Riffat, Faruque
Abstract : Sinonasal adenocarcinoma has traditionally been treated with surgery (craniofacial or endoscopic) and adjuvant radiotherapy. Two large series have demonstrated favourable 5-year survival using surgery with adjuvant topical chemotherapy applied repeatedly over several weeks. The authors describe a novel, transnasal application of topical 5-fluorouracil. However, complete coverage of the frontal region of the anterior skull base can be difficult to achieve with a purely transnasal approach in an outpatient setting. We present a novel adjunct method of delivering chemotherapeutic agents into this key area used in a 37-year-old man with T2N0M0 ethmoid adenocarcinoma. The procedure was well tolerated in an outpatient setting and remains disease free at 3 years postoperatively. We suggest that frontal trephination is a useful adjunct to aid accurate placement of adjuvant topical chemotherapeutic agents in the treatment of sinonasal adenocarcinoma.